Guidelines in disrepute: a case study of influenza vaccination of healthcare workers - Jackie M. Street; Toni N. Delany (Elsevier, 2012)
Abstract Objective: Practice guidelines are an important support tool for health behaviour change, but effective implementation of guidelines can be difficult and the gaps between guidelines and practice may be intractable. This paper examines a neglected but important area; namely, the reasons why problems may develop in the implementation and uptake of practice guidelines. We explore the existence of gaps in the translation of evidence into practice‐based guidelines for health promotion. Approach: Drawing on relevant literature we examine influenza vaccination, in particular, guidelines that advise influenza vaccination for all healthcare workers. We highlight gaps between the actions advised within these guidelines and the relevant evidence, and explore some of the processes that have amplified and obscured this evidence during the development of guidelines. Implications: The processes that underlie the translation of evidence into practice guidelines risk the loss of the nuanced and rich information needed for individual decision‐making. Where evidence is limited, the propagation of evidence‐guidelines gaps, without transparency as to the basis of decision‐making, compromises the credibility of guidelines and puts at risk the benefits that guidelines can provide. Conclusion: We argue that evidence‐guideline gaps may arise because of a range of problems with the nature of the evidence used to justify the guidelines and the way in which that evidence is applied and interpreted. We suggest that these problems may bring potentially useful guidelines into disrepute.